The Australasian Resuscitation In Sepsis Evaluation: FLUid or vasopressors In Emergency Department Sepsis, a multicentre observational study (ARISE FLUIDS observational study): Rationale, methods and analysis plan. (22nd January 2019) - Keijzers, Gerben; Macdonald, Stephen PJ; Udy, Andrew A; Arendts, Glenn; Bailey, Michael; Bellomo, Rinaldo; Blecher, Gabriel E; Burcham, Jonathon; Delaney, Anthony; Coggins, Andrew R; Fatovich, Daniel M; Fraser, John F; et al.
Abstract: Objective: There is uncertainty about the optimal i.v. fluid volume and timing of vasopressor commencement in the resuscitation of patients with sepsis and hypotension. We aim to study current resuscitation practices in EDs in Australia and New Zealand (the Australasian Resuscitation In Sepsis Evaluation: FLUid or vasopressors In Emergency Department Sepsis [ARISE FLUIDS] observational study). Methods: ARISE FLUIDS is a prospective, multicentre observational study in 71 hospitals in Australia and New Zealand. It will include adult patients presenting to the ED during a 30 day period with suspected sepsis and hypotension (systolic blood pressure <100 mmHg) despite at least 1000 mL fluid resuscitation. We will obtain data on baseline demographics, clinical and laboratory variables, all i.v. fluid given in the first 24 h, vasopressor use, time to antimicrobial administration, admission to intensive care, organ failure and in‐hospital mortality. We will specifically describe (i) the volume of fluid administered at the following time points: when meeting eligibility criteria, in the first 6 h, at 24 h and prior to vasopressor commencement and (ii) the frequency and timing of vasopressor use in the first 6 h and at 24 h. Screening logs will provide reliable estimates of the proportion of ED patients meeting eligibility criteria for a subsequent randomised controlled trial. Discussion: This multicentre, observational study will provide insight into current haemodynamic resuscitation practices in patients with sepsis and hypotension as well as estimates of practice variation and patient outcomes. The results will inform the design and feasibility of a multicentre phase III trial of early haemodynamic resuscitation in patients presenting to ED with sepsis and hypotension.